Moving in the right direction? Maize productivity and fertilizer use and use intensity in Ghana - Chapoto, Antony; Ragasa, Catherine (International Food Policy Research Institute, 2013)
Using cross-sectional data on 630 maize farmers and 645 maize plots in Ghana, this paper provides empirical evidence on the responsiveness of maize yield to fertilizer use and use intensity and the economics of fertilizer use with or without subsidy. Similar to previous studies in Ghana and Africa south of the Sahara, the results show that there is a statistically significant maize yield response (that is, 1 kilogram of nitrogen leads to a yield increase of 22 kilograms per hectare).